2021
DOI: 10.1007/s11218-021-09635-w
|View full text |Cite
|
Sign up to set email alerts
|

Do adolescents want death to be included in their education?

Abstract: This study sets out to ascertain adolescents' attitudes and opinions towards death education. To this end two instruments were designed and validated: the 'Death Education Attitudes Scale-Students' and the 'Death Education Questionnaire-Students'. The total sample comprised 1897 secondary school students aged 12-19. Participants showed moderately positive attitudes towards death education. Variables such as gender, age and religious beliefs influenced results. Death is not unfamiliar to adolescents; on the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Regarding the representation of death, the first validation of the TDRS with Italian adults presented an average score that did not express any clear preference for death as a passage or death as annihilation [23]. In the present study, we confirmed the results of other studies that used the TDRS with adolescents [44,45]; that is, the children's total average scores suggested a representation of death as annihilation. No sex differences were observed in the initial validation of the TDRS [23], but some were observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the representation of death, the first validation of the TDRS with Italian adults presented an average score that did not express any clear preference for death as a passage or death as annihilation [23]. In the present study, we confirmed the results of other studies that used the TDRS with adolescents [44,45]; that is, the children's total average scores suggested a representation of death as annihilation. No sex differences were observed in the initial validation of the TDRS [23], but some were observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study showed that the healthier the family, the more supportive the parents are of death education, which aligns with the existing research results. In other studies, improving family health has been shown to enhance parents’ understanding and acceptance of death, thereby allowing them to recognize and attach more importance to death education ( 61 ). Since the family environment is the environment in which individuals first face death, communication, and support among family members play a very important role in dealing with the emotions and perceptions of death ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, improving family health has been shown to enhance parents’ understanding and acceptance of death, thereby allowing them to recognize and attach more importance to death education ( 61 ). Since the family environment is the environment in which individuals first face death, communication, and support among family members play a very important role in dealing with the emotions and perceptions of death ( 61 , 62 ). In healthier families, parents who communicate with their children, offering respect and encouragement, are more willing to help their children improve their understanding of death through death education.…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness research can be evaluated from different perspectives and levels, including knowledge, attitude, skills, practice, etc. [12][13]. The following are some common methods and evaluation indicators of the effectiveness of death education for medical students:…”
Section: Effectiveness Of Death Educationmentioning
confidence: 99%